Assessment of production vulnerability and food sufficiency in the southeastern parts of Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2019)
In a subsistence agrarian economy of Bangladesh, domestic food production has an important role to play in the quest for food security. The productivity in the agricultural sector is critically important if agricultural production is to increase at a sufficiently rapid rate to meet escalating demands for food. Bangladesh has pursued for decades a strategic goal of self-sufficiency in rice production. The country passed a major milestone in its efforts to achieve food security in the sense of rice grain availability at the national level at the end of the 1990s. Whatever progress been made would be difficult to sustain it due to high vulnerability of climatic shocks and the growing pressure of population on scarce natural resources thus, yet food security has not been achieved. The present study finds that, rice production is secure in Feni district from Chittagong division. Because rice production is greater than the consumption. On the other hand, Chandpur and Cox’s Bazar district shows production insecurity in the very recent years. But Chittagong district has the production insufficiency from the past to present, because the production is insufficient to meet the demand of the vast population in this area. The study reveals that, the production of Aus rice will be increased in the next 5 years in Chittagong district. Aman rice production will be increased in the next 5 years in the districts namely Feni. Again, Boro rice production will be increased in the next 5 years in the districts namely Cox’s bazar and Feni districts.Asian Australas. J. Food Saf. Secur. 2019, 3(2), 77-84